FAKTOR-FAKTOR YANG MEMENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PADA PERUSAHAAN DIBIDANG PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gracia Gunawan, Prima Apriwenni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
In the companyâ€™s efforts to achieve profit, companies often pay less attention to the impact of their activities. This matter can cause global warming. To prevent these problems, the law is issued that requires every company to do some activities that are environmentally friendly. This activity is expressed throuth the corporate social responsibility disclosure. The purpose of this research to test whether profitability, liquidity, leverage, and media exposure have a positive influence to corporate social responsibility disclosure. The object of this research is a mining company listed in Indonesia Stock Exchange year 2014-2016 with the unit observation is annual financial statements with a total sample of a company is 36 companies. The research method used is observation method with an observation to company data. Based on test results, liquidity and media exposure significantly influence CSR disclosure, while profitability and leverage had no significant influence to CSR disclosure.Â Keyword: Corporate Social Responsibility, Disclosure, Profitability, Liquidity, Leverage, Media Exposure